Object – Body – Flashback in “The Seagull” by Michael Mayer - Niagolova, Natalia (Slavica, 2020)
The article features the transformation mechanisms of Chekhov’s play “The Seagull” in its film adaptation of 2018 by Michael Mayer. The director’s concept activates the opposition “memory – forgetfulness” and this is based on composition-visual reminiscences, i.e. flashbacks. The world of objects and the body discourse in the film complies with that specific film story of nostalgia in which the past is not simply going back to the things the characters were through, but also as a new reading of Chekhov’s intertextuality in the context of Anglo-Saxon cinema culture as well as a stylized memory of the Russian classic writer and his times.